Perkawinan Di Bawah Umur Ditinjau Berdasarkan Undang-Undang Nomor 16 Tahun 2019 Tentang Perubahan Atas Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan Di Kabupaten Kuantan Singingi - Putri, Amelia Jelita; Bachtiar, Maryati; Hasanah, Ulfia (Jurnal Ilmiah Wahana Pendidikan, 2026)
Marriage is a physical and spiritual bond between a man and a woman as husband and wife with the goal of forming a happy and eternal family (household) based on the One Almighty God. In traditional marriages, relatively young couples are sometimes encountered. Therefore, this study aims to examine the practice of underage marriage in Kuantan Singingi Regency and the legal consequences of underage marriage without court dispensation. This type of research can be classified as sociological juridical research. The research locations were the Kuantan Singingi Regency Religious Court, the Benai Religious Affairs Office, the Cerenti Religious Affairs Office, the Baserah Religious Affairs Office, and the Pangean Religious Affairs Office. The population and sample included all parties related to the research problem. This study used primary and secondary data sources, and data collection was conducted through interviews. From the results of the research problem, there are two main things that can be concluded. First, the implementation of underage marriage is carried out with dispensation and without dispensation, the urgent reasons for the Religious Court to grant dispensation for underage marriage are pregnancy outside of marriage, avoiding adultery, mutual agreement, and economic factors. Second, the legal consequences of underage marriage whose marital status is not registered are administratively invalid, do not receive legal protection as husband and wife, children born as children out of wedlock, and violate the minimum age limit for marriage. The author's suggestion is first, it is hoped that the Religious Court of Kuantan Singingi Regency must be more selective in granting marriage dispensation, by ensuring the reasons submitted are truly urgent and consider the best interests of the child. Second, it is hoped that in preventing underage marriage in Kuantan Singingi Regency, legal education is needed for the community.